The effect of an alcoholic extract of fruits of Jatropha curcas on some of the reproductive processes in the female albino rat (Rattus norvegicus) - Afriyie, James (2012)
A thesis presented to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, Ghana, in partial fulfilment of the requirements for the Master of Science (Reproductive Biology) Degree